Raw-appearing Restructured fish models made with Sodium alginate or Microbial transglutaminase and effect of chilled storage - Moreno,Helena (2013)
Restructuring by adding Sodium Alginate or Microbial Transglutaminase (MTGase) using cold gelation technology make it possible to obtain many different raw products from minced and/or chopped fish muscle that are suitable for being used as the basis of new restructured products with different physicochemical properties and even different compositions. Special consideration must be given to their shelf-life and the changes that may take place during chilling, both in visual appearance and physicochemical properties. After chilled storage, the restructured models made with different muscular particle size and composition at low temperature (5 °C), it was observed that microbial growth limited the shelf-life to 7-14 days. Mechanical properties increased (p < 0.05) during that time, and higher values were observed in samples elaborated by joining small muscle particle size than in those elaborated by homogenization. There was no clear increase in the cooking yield and purge loss, and no significant colour change (p > 0.05) was detected during storage.